İstanbul Bayezid camii taş süslemeleri - Cıda, İsa (My University, 2005)
İstanbul'da II. Bayezid tarafından yaptırılan Bayezid Camii 1500- 1505 yılları arasınsa inşa edilmiştir. Bu tezde, İstanbul Bayezid Camii taş süslemeleri incelenmiştir. Minareler, kapılar, avlu, şadırvan, duvar yüzeyleri, hünkar mahfili, müezzin mahfili, kadınlar mahfili, mihrab, minber, sütunlar incelendi. Taş üzerindeki süslemelerin fotoğrafları çekildi, çizimleri yapıldı, ölçüleri alındı, anlamlandırıldı. Malzeme olarak çeşitli mermerler, granit, köfeki taşı, porfir ve macunlar kullanılmıştır. Genellikle geometrik ve bitkisel motifler, rumiler, hatailer görülmektedir. Tez dört bölümden meydana gelmektedir. Birinci bölümde süslemenin önemi, tezde izlenen yöntem ve bu konudaki yayınlar incelendi. İkinci bölümde II. Bayezid döneminin sosyo- politik yapısı, Bayezid Camii ve dönemin taş dekorasyonu üzerinde duruldu. Üçüncü bölüm tezin ana bölümünü oluşturmaktadır ve burada caminin taş dekorasyonu incelendi. Dördüncü ve son bölümde İstanbul Bayezid Camii taş dekorasyonunun etkileri üzerinde duruldu. Fotoğraflar, gravürler, planlar ve çizimler tezin arkasına eklendi. İstanbul Bayezid Camii, Osmanlı Klasik Döneminin başlangıç eseri olduğunu taş dekorasyonuyla kanıtlamıştır. Caminin süslemelerinin belli bir olgunluğa ulaştığını görmekteyiz. Name and Surname : İsa CIDA Field: Turkish Art Supervisor : Professor Selçuk MÜLAYİM Degree Awarded and date: Master- September 2005 Bayezid Mosque, Stone Adornment

STONE ADORNMENT OF ISTANBUL BAYEZID II MOSQUE The Bayezid Mosque was built in İstanbul by II. Bayezid between 1500 and 1505. In this thesis, the stone adornment of the İstanbul Bayezid Mosque is scrutinized. The Minarets, the doors, the courtyard, the tanks of water, the surfaces of walls, the arde of hunkar, the arde of muezzin, the circle of women, the miche, the pulpit and the colums are scrutmized.The adornments on the walls are taken photos, drawn, measured and interpreted. As materials, different wnds of marbles, granites, köfeki, porphyres and pastes were used. Mostly, geometrical and herbal motives, rumi and hatai were presented. The thesis is farmed of four parts. In the first part; the importance of adornment, the ways that are fallowed and the publications on the subjects are studied. In the second part; the sociopolitical state of the age of II. Bayezid, the Bayezid Mosque and the stone adornment and decoration of the age are examined. The thirt port forms the main port of the thesis and in this port, the stone decoration of the mosque is scrutinized. In the fourth and also the lost port, the effects on the stone decoration of İstanbul Bayezid Mosque are studied. Photos, engravings, plans and drawings are added to the thesis. The İstanbul Bayezid Mosque proved it self as the starting building on the Ottoman Classical Age by the help of its stone decoration. It is obvious that the adornment of the mosque has been mellowed and is an important step forward.
Keywords: Camiler ve minareler; Camiler, Mimari; Dini ve benzeri amaçlı yapılar; Güzel ve dekoratif sanatlar; Mimari, İslam; Mimarlık; Taş Süslemeler